Deriving Market Expectations for the Euro-Dollar Exchange Rate from Option Prices - Krichene, Noureddine (IMF Working Papers; Working Paper ;, 2004)
Option prices provide valuable information on market expectations. This paper attempts to extract market expectations, as conveyed by an implied risk-neutral probability distribution, from option prices for the dollar-euro exchange rate. Returns' volatilities are inferred from observed and interpolated option prices. To address robustness, two distributions, one from actual data and the other from interpolated data, were computed. The main conclusion of the paper is that traders have wide-ranging expectations, and large movements in either direction would not occur as a surprise. The main implication for monetary policy is that should markets become too volatile, then intervention may be required.